NY Art Now : The Saatchi Collection - The Saatchi Gallery, London; Bickerton, Ashley; Bleckner, Ross; Cameron, Dan; Dunham, Carroll; Gober, Robert; Halley, Peter; K.O.S.; Koons, Jeff; McCollum, Allan; Rollins, Tim; Steinbach, Haim; et al. (Milano : Giancarlo Politi Editore, 1987)
Bickerton, Ashley ; Bleckner, Ross ; Dunham, Carroll ; Gober, Robert ; Halley, Peter ; Hsu, Tishan ; Kessler, Jonathan ; Koons, Jeff ; Lasker, Jonathan ; McCollum, Allan ; Rollins, Tim & K.O.S. ; Schuyff, Peter ; Starn, Doug & Mike ; Steinbach, Haim ; Taaffe, Philip ; Vaisman, Meyer
biog., ind. tent., gr. tent., bibliog. p. 207-232
Engels
boek